Development of Solar Radiation Intensity Measurement Tool Using BH1750 Sensor Based on The Internet Of Things with Smartphone Display - Alex Sandryadi; - Yulkifli; - Yohandri; Heron Tarigan (PILLAR OF PHYSICS, 2022)
This research aims to determine the performance and design specifications of the system measuring the intensity of solar radiation using BH1750 sensor based on  internet of things with smartphone display. In agriculture, Soil fertility is closely related to maximum yield. Soil fertility and plant growth are determined by many factors, one of the most important is the intensity of solar light. The tools used in the field are still quite simple, where to measure the intensity of solar light still using a lux meter and even though the data read  from a digital lux meter cannot be seen anywhere. This measuring instrument is built using the BH1750 sensor, namely as a sensor of solar radiation intensity, NodeMCU ESP8266 as a microcontroller programmed using the Arduino IDE programming language to access the internet network so that it can be sent to the Thingspeak server, and data from Thingspeak is displayed on an Android smartphone using the APP Inventor application, and the data can be displayed. displayed on the Thingspeak server, and also can be stored in memory Micro SD. Based on the results of the development of a measuring instrument for the intensity of solar radiation, it is obtained Data where the highest solar intensity occurs on average between 02.55 – 03.38 UTC ± 0 and between 04.00 – 06.20 UTC ± 0, Each plants has a different need for solar intesity  for photosynthesis because the more solar that is sufficient on the plant, so the plants it will become optimal growth.